Resilient businesses for sustainability : advances in human resource management and marketing : part B - Misra, Rajnish Kumar; Purankar, Shriram A.; Goel, Divya; Kapoor, Shivani; Sharma, Ridhima B. (Advanced series in management ;, 2024)
The modern era is marked by intricate disruptions originating from diverse sources, carrying long-term implications. In the face of this formidable predicament, organizations find themselves compelled to embrace new management practices suitable for this ever-changing landscape. As the focus shifts to resilience, organizational leaders strive to cultivate robust entities capable of bouncing back stronger, ensuring their prosperity in this challenging environment. In Resilient Businesses for Sustainability: Advances in Human Resource Management and Marketing, Part B, a cross-section of global academics highlight the paths taken by various organizations to create resilient enterprises. This fascinating work explores how companies adapt, innovate, and integrate data into their processes while embracing transformative technologies in order to overcome challenges in different spheres of business. By conquering multifaceted obstacles across various domains of business, these organizations forge sustainable competitive advantages that propel growth and create market leadership. With contributions from a diverse cross-section of scholars worldwide, this second volume provides invaluable insights into the role of Human Resource for sustainability and Marketing for building resilient businesses. Offering a comprehensive examination of how resilience is harnessed to build businesses capable of withstanding adversity, this book serves as an indispensable resource for researchers, practitioners, and leaders seeking to thrive in the turbulent era we inhabit.